2009
DOI: 10.1051/0004-6361/200912705
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbon selected galaxies

Abstract: Context. This is the fourth in a series of papers based on the ISOCAM Parallel Survey at 6.7 μm. While the first three papers have been devoted to active galactic nuclei (AGN), here we report on emission-line galaxies without AGN signatures in their optical spectra. Aims. Polycyclic aromatic hydrocarbon (PAH) emission has been found in both starbursts and modestly starforming galaxies, but the relation between starforming activity and PAH luminosity is still a matter of debate. The different correlation degree… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Results from SINGs have indicated that the use of PAH emission for estimating star formation rates may be uncertain by a factor of ∼10 (Dale et al 2005;Calzetti et al 2007). This conclusion is also supported by Tacconi-Garman et al ( 2005) who find strong variations in the PAH to stellar continuum ration in nearby starburst galaxies, as well as Haas et al (2009) who find a range in the L f ir /L 6.3µm of a factor of 10 for a sample of PAH selected galaxies from the ISOCAM parallel survey. In Figure 14 we plot L 11.3µm /νL ν 60µm for the 2Jy and 3CRR objects from the current study, along with comparison samples of LIRGs and starburst objects of similar far-IR luminosity taken from Brandl et al (2006), and starburst-dominated ULIRGs taken from the study of Veilleux et al (2009).…”
Section: The Origin Of the Far-ir Emissionsupporting
confidence: 71%
“…Results from SINGs have indicated that the use of PAH emission for estimating star formation rates may be uncertain by a factor of ∼10 (Dale et al 2005;Calzetti et al 2007). This conclusion is also supported by Tacconi-Garman et al ( 2005) who find strong variations in the PAH to stellar continuum ration in nearby starburst galaxies, as well as Haas et al (2009) who find a range in the L f ir /L 6.3µm of a factor of 10 for a sample of PAH selected galaxies from the ISOCAM parallel survey. In Figure 14 we plot L 11.3µm /νL ν 60µm for the 2Jy and 3CRR objects from the current study, along with comparison samples of LIRGs and starburst objects of similar far-IR luminosity taken from Brandl et al (2006), and starburst-dominated ULIRGs taken from the study of Veilleux et al (2009).…”
Section: The Origin Of the Far-ir Emissionsupporting
confidence: 71%